Collection and marketing of non-timber forest products by Chepang community in Nepal - Piya, Luni; Maharjan, KL; Joshi, NP; Dangol, DR (Journal of Agriculture and Environment, 2013)
Chepangs are highly marginalized indigenous nationalities of Nepal, who live nearby the forests that are rich in Non-timber Forest Products (NTFPs) of commercial importance. These NTFPs can be a potential source of income for Chepangs. This study describes the role of Chepangs in the marketing channel of those NTFPs and analyses the household socio-economic characteristics that influence the collection and marketing of NTFPs by Chepangs in Shaktikhor VDC of Chitwan district using backward multiple regression method. Empirical evidences show that collection and marketing of NTFPs is not an attractive source of income especially for those relatively better-off Chepang households who possess higher landholdings, food self-sufficiency, and income from other alternative sources. This is because the current price offered for the NTFPs collected by the community is very nominal, that do not even cover the labour costs involved. Praja Cooperative Limited (PCL), a Chepang community based institution in Shaktikhor, is struggling to provide better prices for Chepangs. However, it is facing challenges due to limited institutional management capacity of Chepangs. Further empowerment of PCL can contribute to improve the bargaining power of Chepang community in NTFP trade. The Journal of Agriculture and Environment Vol:12, Jun.2011, Page 10-21 DOI: http://dx.doi.org/10.3126/aej.v12i0.7558